2016
DOI: 10.4103/0019-5413.193490
|View full text |Cite
|
Sign up to set email alerts
|

Functional and computed tomography correlation of femoral and tibial tunnels in single-bundle anterior cruciate ligament reconstruction

Abstract: Background:An accessory anteromedial portal (AAMP) has been shown to be effective in placing an anatomically ideal femoral tunnel. It is well known that this is due to the independent femoral drilling which is possible with the AAMP. However very little is known regarding the significance of this reconstruction technique in influencing the functional outcomes of anatomic anterior cruciate ligament reconstruction (ACLR). This study documents the influence of tibial and femoral tunnel positions on functional out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
2
1
0
Order By: Relevance
“…In our study, there were no intraoperative and postoperative complications similar to those reported by Zhang et al [ 29 ] and Mathai et al [ 30 ]. Kumar et al [ 31 ] reported complications in seven patients (stiffness in two patients, infection in two, femoral tunnel blow-out in one, and graft re-rupture in one patient) with a minimum of 24 months of follow-up, which is longer than our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, there were no intraoperative and postoperative complications similar to those reported by Zhang et al [ 29 ] and Mathai et al [ 30 ]. Kumar et al [ 31 ] reported complications in seven patients (stiffness in two patients, infection in two, femoral tunnel blow-out in one, and graft re-rupture in one patient) with a minimum of 24 months of follow-up, which is longer than our study.…”
Section: Discussionsupporting
confidence: 90%
“…The baseline demographic data, i.e., mean age, ranged between 26.83 ± 7.50 years, which was similar to previous studies [29][30][31]. The age group of fewer than 30 years comprised 22 patients (75.87%), confirming the association of ACL years, especially in young individuals.…”
Section: Discussionsupporting
confidence: 86%
“…However, deep-knee bending is required when creating the femoral tunnel using this method, and insufficient femoral tunnel length and iatrogenic femoral chondral tear are potential complications. 36,56,64,67,82,91 The transtibial technique is the most traditional technique used to create the femoral ACL tunnel. Although, there is no need to worry about the iatrogenic problems that are potential complica-tions in the transportal technique, it is relatively demanding to reach the center of the native ACL footprint using this technique.…”
Section: Discussionmentioning
confidence: 99%